A profile for metallurgical mining activity of zinc in Perú and the human development index 1995-2014 - Ospino Edery, Ysaac (2015)
The article brings us to one of the most representative products of our metallurgical activity such as zinc, to the economic and social contribution of this commodity, since it is located in importance after copper and gold. The topics considered are total investment, and zinc related to the study period, output per strata (Large, Medium and Small Mining), in both TMS and TMF.So the fate of the same, in which is seen our extreme dependence on markets such as China and South Korea.In the final analysis they are considered aspects related to the contribution of mining to GDP to total GDP, such is the case that the former grows by about 10 times, compared to only about 5 times in the second. So it is the relationship between the productive activity of zinc mining and the Index of Human Development and Poverty that is that in the study period production is multiplied several times, while the mentioned indices had no major changes.